PENGARUH KONSENTRASI BELAJAR DAN KEJENUHAN BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA - Yoka Agry Sativa; Joko Purwanto (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
ABSTRACTLearning concentration and burnout are interrelated in the learning process. Low learning concentration and high learning saturation will affect learning achievement. This study aims to determine 1) the effect of learning concentration on mathematics learning achievement; 2) the effect of learning burnout on mathematics learning achievement; 3) the effect of learning concentration and burnout on mathematics learning achievement. This research was conducted at SMP Negeri 3 Sumbang using quantitative with the ex post facto method. The population in this study was seventh-grade students of SMP Negeri 3 Sumbang. The research sample was 110 which was determined using simple random sampling with random selection using Isaac and Michael tables with an error rate of 5%. Data collection techniques used questionnaires and tests that had passed the validity and reliability tests. The data were examined using prerequisite tests; the normality test, multicollinearity test, heteroscedasticity test, and linearity test. A multiple linear regression model and the hypotheses testing were then employed; the correlation coefficient, the coefficient of determination, the partial test (t-test), and the simultaneous test (F test). The linear regression model formed was Y = 71.354 + 0.422X1 - 0.950X2. The results of the study stated that 1) learning concentration had a positive effect on mathematics learning achievement by 14.7%; 2) learning burnout contributed a negative effect on mathematics learning achievement by 52.1%; 3) learning concentration and burnout had a significant effect on mathematics learning achievement by 66.7%.